The Effectiveness of The Multiplication Finger Technique on Students' Understanding of Division Operation Material in Public Elementary School 2 Kaliwungu - Setiawan, Arif Wahyu; Purwandari, Ristiana Dyah (Proceedings Series on Social Sciences & Humanities, 2024)
Spelling arithmetic division is one of the things that is difficult in mathematics, especially in elementary schools. This is evidenced by the low evaluation or assessment results on the load. With this concern, the authors conducted research and trials regarding this matter in order to overcome the difficulties and obstacles experienced by students at SD Negeri 2 Kaliwungu, Mandiraja sub-district, Banjarnegara district. The action taken is by applying the Multiple Finger Technique (Teknik Jari Kelipatan). According to L. James Havery (2000) technique is a logical and rational procedure for designing a series of components that are related to each other with the intention of functioning as a unit in an effort to achieve a predetermined goal. While this multiple finger is the use of the fingers in the process of calculating division as a result. The application of this technique is felt to be very effective and able to generate students' understanding in SD Negeri 2 Kaliwungu regarding distribution so that the achievement and enthusiasm of students is increasing.